DESIGN AND MOLECULAR DOCKING OF SULFONAMIDE DERIVATIVES - BARMAN, KAMALLOCHAN; DAS, GARGI; KALITA, JUN MONI; DASGUPTA, PAYAL (International Journal of Current Pharmaceutical Research, 2021)
Objective: Sulfonamides are a sulfa-related group of antibiotics, which are used to treat bacterial infections and some fungal infections. Some sulfonamides are also devoid of antibacterial activity, such as thiazide diuretics, etc. In this study, an effort was made to find out some novel and potent Sulfonamide derivatives as diuretic agents. Methods: Here, 30 three-dimensional sulphonamides are designed and docking simulation with PDB ID 1AZM which was downloaded from www. rcsb. org. All the molecules were also screened through a preliminary property filter (Molinspiration Property Calculator). Results: Among the 30 different molecules designed, 5 molecules were found to have a very good affinity towards the target protein. Conclusion: These molecular properties define if a molecule can be orally active in our body.